Perbedaan Penggunaan Model pembelajaran Kooperative tipe Students Team-Achievement Divisions (STAD) dengan Team Assisted Individualition (TAI) terhadap Hasil Belajar Perkalian dan Pembagian Pecahan dan Desimal di Kelas V Sekolah Dasar Gugus I Sungai Pua - RAMADANI, FEBRIMA; Masniladevi, Masniladevi; Zuryanty, Zuryanty (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study aims to find out the differences between the use of Student Team-Achievement Divisions (STAD) type Cooperative learning models and Team Assisted Individualition (TAI) on the results of Multiplication and Decimal Multiplication and Distribution. This type of research is an experiment using a quasi-experimental design with the pretest-posttest non-equivalent group. The sample in this study was the VA class and VB SD N 02 Sariak. The study sample consisted of 21 VA class students as the STAD model group and 21 VB class students as the selected TAI model group based on purposive sampling technique. The results of the calculation of the research data used is the t-test obtained by t count 8.11> t table 1.68385 at the level of α 0.05. This means that the use of the STAD model is better than the TAI model on the learning outcomes of multiplication and division of fractions and decimals. Keywords  : STAD Cooperative, TAI, Students Learning Outcomes,Mathematic